2018
DOI: 10.1002/aenm.201801234
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Multilayer Encapsulation for Perovskite Photovoltaics

Abstract: An encapsulation system comprising of a UV‐curable epoxy, a solution processed polymer interlayer, and a glass cover‐slip, is used to increase the stability of methylammonium lead triiodide (CH3NH3PbI3) perovskite planar inverted architecture photovoltaic (PV) devices. It is found this encapsulation system acts as an efficient barrier to extrinsic degradation processes (ingress of moisture and oxygen), and that the polymer acts as a barrier that protects the PV device from the epoxy before it is fully cured. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 55 publications
0
69
0
Order By: Relevance
“…Despite the impressive high efficiency, the stability of PSCs lags far behind the requirement for future commercialization. [16][17][18][19][20] However, there is still great challenge to obtain long-term stability and further investigation is urgent. [3,9,10] Efforts have been carried out to improve the stability of PSCs such as solvent engineering, [11][12][13] interface engineering, [14,15] composition engineering, and encapsulation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the impressive high efficiency, the stability of PSCs lags far behind the requirement for future commercialization. [16][17][18][19][20] However, there is still great challenge to obtain long-term stability and further investigation is urgent. [3,9,10] Efforts have been carried out to improve the stability of PSCs such as solvent engineering, [11][12][13] interface engineering, [14,15] composition engineering, and encapsulation.…”
Section: Introductionmentioning
confidence: 99%
“…Continued progress in stability remains a topic of importance along the path to industrial application [3][4][5] . Encapsulating PSCs to protect against oxygen and moisture is a straightforward method to stabilize these devices [6][7][8] ; however, some important sources of instability are not overcome using extrinsic stabilization approaches such as encapsulation 9 .…”
mentioning
confidence: 99%
“…[19][20][21][22] For example, it has been shown that ultra-thin layers of poly(triarylamine) (PTAA) or poly(4butylphenyldiphenylamine) (poly-TPD) can be used as HTMs to achieve remarkable V OC and fill factor (FF). [22][23][24][25] Here however, our architecture requires that the charge-transport layers are easily evaporable.…”
Section: Papermentioning
confidence: 99%